Analiz pokazatelej sorevnovatel'noj dejatel'nosti vysokokvalificirovannych legkoatletov v bege na 110 metrov s bar'erami - Mirzoev, O. M.; Kalinina, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
This article presents a variety of indicators that characterize the structure of competitive activities of highly qualified athletes specializing in the 110 meter hurdles. All athletes participated in the final race of the 17 World Championships in Athletics (2019, Doha, Qatar).At the end of the 2019 competition season, six of the finalists were ranked among the top ten hurdlers in the world. We analyzed the dynamics of athletes` performances at four World Championships (2013-2019), considered the number of competitions and starts, their distribution in the annual cycle, and showed the number of days after which the peak of athletic form was reached.Based on the information received, it was determined that, for example, S. Shubenkov and P. Martino-Lagart performed the most at the world Championships during the analyzed period, and it takes from 26 to 111 days for the studied hurdlers to reach the peak of their athletic form.Also, the analysis of competitive activities showed the types of athletics, except for the main ones, which are preferred by the finalists. The data obtained indicate that the world champion in the 2019 season, unlike others, actively competed in six sports, including those not related to hurdling.All this indicates an individual approach to building not only the training process, but also to competitive activities, and the competitions themselves can act (with proper planning) as an important argument in the preparation of an athlete.